Dentists' Awareness in Emergency Management of Traumatic Dental Injuries: Implications for Improved Care - Ahmadi, Masoumeh; Seidkhani, Hossein; Tila, Ahmad (Journal of Dental School, 2025)
Objective(s): The current study aimed to investigate the level of dentists' knowledge and understanding of traumatic dental injuries (TDIs) to pinpoint specific areas where emergency dental care protocols and practices can be enhanced and optimized. Methods: A cross-sectional survey of 70 dentists in the city of Ilam, Iran, explored their knowledge, attitudes, and practices concerning TDIs. Data were collected using a researcher-developed questionnaire encompassing demographic information, a history of trauma-related training, and responses to 15 TDI-related questions, which were scored according to pre-defined criteria. Statistical analysis included analysis of variance (ANOVA), Tukey's honestly significant difference [HSD] test, Chi-square test, and t-test at p<0.05. Results: While gender did not demonstrate a statistically significant correlation with knowledge levels (p = 0.19), dentists who frequently treated TDI exhibited significantly higher awareness (p = 0.04). Prior training in TDI management, history of retraining, and years of practice exhibited no significant influence on awareness scores. Overall, participants achieved a mean accuracy of 43.4% on TDI-related questions, and no participant demonstrated a lack of basic knowledge. Conclusion: This study demonstrated a significant deficiency in dentists' understanding of emergency management protocols for TDIs, particularly concerning the diagnosis of intricate cases and the handling of associated complications. This highlighted the necessity for continued professional development and training in emergency dental care.